2019
DOI: 10.1039/c9ra07828b
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow lattice thermal conductivity and high thermoelectric performance of monolayer KCuTe: a first principles study

Abstract: The excellent thermoelectric performance of monolayer KCuTe is discovered by first-principles study for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…These values are realized as the carrier concentrations in the range of 1 × 10 12 to 3 × 10 12 cm –2 by many methods, such as doping, applying strain, changing the generation environment, and so on. The ZT values of the InBrSe monolayer are much higher than that of previously reported FeOCl-type monolayers and many excellent 2D TE materials, such as the KCuTe monolayer (2.71 at 700 K), 2D KAgSe (2.08 at 700 K), the δ-Cu 2 S monolayer (1.33 at 800 K), and so on. More importantly, we find that the maximum energy conversion efficiency of the InBrSe monolayer can reach 26.1%, which is comparable to that of the traditional heat engine.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These values are realized as the carrier concentrations in the range of 1 × 10 12 to 3 × 10 12 cm –2 by many methods, such as doping, applying strain, changing the generation environment, and so on. The ZT values of the InBrSe monolayer are much higher than that of previously reported FeOCl-type monolayers and many excellent 2D TE materials, such as the KCuTe monolayer (2.71 at 700 K), 2D KAgSe (2.08 at 700 K), the δ-Cu 2 S monolayer (1.33 at 800 K), and so on. More importantly, we find that the maximum energy conversion efficiency of the InBrSe monolayer can reach 26.1%, which is comparable to that of the traditional heat engine.…”
Section: Discussionmentioning
confidence: 70%
“…Exploring new high-performance 2D TE materials is a very attractive way, and some new types excellent 2D TE materials have been reported, such as ZrS 3 (ZT is 2.44), Penda Silicon (ZT is 3.4), TiS 3 (ZT is 3.1), KCuTe (ZT is 2.71), KAgSe (ZT is 2.08), and the HfN 2 /MoTe 2 heterojunction (ZT is 2.28) . Recently, theoretical research has shown that FeOCl-type monolayers can achieve good TE performance due to their unique electronic and phonon transport properties. Moreover, it has been found that FeOCl-type 2D materials have a multi-band valley in the conduction band.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, considering only LA phonon scattering using the deformation potential theory, a large number of thermoelectric materials with promising ZT values have been predicted, including a CdS monolayer (0.78 at room temperature), CdSe monolayer (0.5 at room temperature), 2D KAgSe nanosheet (2.08 at 700 K), monolayer penta-silicene (3.4 and 3.0 for P- and N-type at room temperature), Sb 2 Si 2 Te 6 monolayer (4.52 at room temperature for P-type), 2D heterobilayer (1.1 and 0.3 for P- and N-type doping at 300 K), N-type TiS 3 monolayer (3.1 and 0.5 along the Y and X axes), and so forth. Furthermore, the ZT values of KCuTe (2.71 at 700 K) and monolayer HfN 2 (2.28) are predicted using a simpler constant relaxation time approximation. However, it should be noted that the use of the deformation potential theory alone will mostly provide overestimated ZT values.…”
Section: Resultsmentioning
confidence: 99%
“…Materials with high and low thermal conductivities are crucial for the application ranging from the thermal management of electronic devices to energy sustainable development. , For example, on the one hand, with the increasing demand for high-performance optoelectronic devices, heat dissipation has become a noticeable factor limiting their performances, indicating that exploring materials of novel high thermal conductivity is an important field. On the other hand, as far as energy utilization, thermoelectric materials with low thermal conductivity can efficiently convert waste heat from solar energy, factories, or electrical equipment into electric energy. Therefore, it is extremely significant to specify the materials with target high or low thermal conductivity from tens of millions of material candidates.…”
Section: Introductionmentioning
confidence: 99%